Replication data for: Modern pollen data for North America - Johanne Whitmore, Konrad Gajewski, Mike Sawada, J.W. Williams, T. Minckley, B. Shuman, P.J. Bartlein, T. Webb, A.E. Viau, S. Shafer, P. Anderson, L. B. Brubaker (Borealis, 2005)
A database of modern pollen for North America and Greenland with associated environmental data.